Screening for bronchial asthma as an effective method of its timely detection in school-age children - O.Ye. Fedortsiv; L.A. Volyanska; E.I. Burbela; N.Yu. Pospikh (Zaslavsky O.Yu., 2018)
An epidemiological study of bronchial asthma was carried out by questioning parents and children of urban and rural areas of the Ternopil region in order to evaluate the prevalence, determination and representation of the main markers of the disease among children of senior and secondary school age. Children underwent detailed history collection, survey developed according to the International Study of Asthma and Allergies in Childhood and objective clinical examination. This fragment of epidemiological studies has shown that the prevalence of bronchoobstructive diseases in the region (5.62 %) differs significantly from official statistics (1.7 %).